THE IMPACT OF FOOD VLOGGER CONTENT ON PURCHASING DECISSIONS : THE MEDIATING ROLE OF VIRAL MARKETING(Survey of Tiktok Users in Sukabumi City) - Ayu Rohmah; Asep Muhammad Ramdan; Tetty Suﬀianty Zafar (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
This study aims to analyze the influence of the attractiveness of food vlogger content on purchasing decisions of MSME products, as well as the role of viral marketing as a mediating variable on TikTok users in Sukabumi City. The background of this study is based on the phenomenon of the increasing use of social media, especially TikTok, as a means ofpromoting MSME products through collaboration with food vloggers. The method used is quantitative with a descriptive and associative approach. Data collection techniques were carried out through online questionnaires distributed to 145 respondents who met certain criteria. Data analysis used Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the help of SmartPLS 4.0 software. The results of the study show that the attractiveness of content has a positive and significant effect on purchasing decisions, both directly and indirectly through viral marketing. Viral marketing has been shown to mediate the relationship between the attractiveness of content and purchasing decisions, which means that interesting content can increase the likelihood of content spreading virally, and ultimately influence consumer purchasing decisions. These findings indicate that content-based marketing strategies and social media have an important role in supporting the promotion of MSME products. This study provides theoretical implications in the development of digital marketing literature as well as practical recommendations for MSMEs and content creators to optimize the potential of social media in reaching consumers more effectively.